Down-regulated of PCDH10 predicts poor prognosis in hepatocellular carcinoma patients. Issue 35 (August 2018) - Bing, Yuntao; Tian, Maolin; Li, Gang; Jiang, Bin; Ma, Zhaolai; Li, Lei; Wang, Liang; Wang, Hangyan; Xiu, Dianrong
Abstract : Abstract: Protocadherin10 ( PCDH10 ), a member of the nonclustered protocadherin family, functions as a tumor suppressor in many cancers. The aim of this study was to evaluate the expression level and prognostic value of PCDH10 in hepatocellular carcinoma (HCC) patients. Quantitative real-time polymerase chain reaction was used to analyze the expression level of PCDH10 in HCC tissues and adjacent nontumor tissues. The association of PCDH10 expression with clinicopathological features of patients was evaluated by chi-squared test. Overall survival was estimated using the Kaplan–Meier method. Besides, the patient prognosis was also evaluated by Cox regression analysis. PCDH10 expression was significantly lower in HCC tissues than that in adjacent nontumor tissues ( P  = .000). Kaplan–Meier curves showed that patients with lower PCDH10 expression had a worse overall survival. Moreover, PCDH10 expression level was associated tumor size ( P  = .005), tumor node metastasis stage ( P  = .002), smoking status ( P  = .000), and drinking status ( P  = .005). Multivariate analysis showed that the expression of PCDH10 ( P  = .000; hazard ratio = 4.784; 95% confidence interval: 2.550–8.977) was an independently associated with poor overall survival rates, as well as smoking status and drinking status. Our findings indicated that the decreased expression of PCDH10 was closely associated with poor prognosis of HCC patients. It might be considered as a valuable biomarker for HCC.